IMPROVING COMMUNITY AWARENESS ON PREVENTION OF COVID-19 TRANSMISSION THROUGH SHARING EXPERIENCES BY NURSES AND SURVIVOR - Andri Setiya Wahyudi; Candra Panji Asmoro; Hakim Zulkarnain; Achmad Tirmidzi (Community Service Journal of Indonesia, 2021)
The situation of the increasingly massive spread of Covid-19 in Indonesia has forced several countries to issue travel restrictions for their citizens entering Indonesia, as well as prohibiting Indonesian citizens from visiting their country. Health promotion is needed that can raise the awareness of Indonesian citizens to adhere to health protocols. This community service activity seeks to increase public awareness by sharing experiences from survivor and nurses of Covid-19 patients at community health services (CHS) and in field hospitals. Health promotion through webinars, which are open publicly and for free, took place on September 29, 2020. Webinars through the Zoom application and broadcast live streaming on Youtube media with the channel name "baca baca baca". The two media were chosen with the intention of making health education activities accessible to many people at any time so that the achievement of the goals could also be broader. The number of participants in Zoom media when conducting the webinar according to the previous plan is at least 50 people (54 people). The number of viewers via Youtube media exceeds the planned output of more than 100 viewers (326 people) in three months. Awareness improvement of the general public in complying with health protocols in preventing Covid-19 transmission is built through a good perception of this. Good perceptions are built through correct knowledge. The webinar method has also proven not to be an obstacle to providing health promotion to the public.